کافر اور مشرک رشتہ داروں سے حسن سلوک ، سیرت النبی ﷺ کی روشنی میں: Be kind to relatives of infidel and Polytheists in the light of Seerat Ul Nabi ﷺ - Ehtisham ul Haq (MEI, 2023)
I have described five types of infidels, about which there are different rules in islam. I would like to mention few incidents in which the Prophet (SWS) acted in the case of disbelievers. He will take care of the man of his part in his faction. But if the Prophet of Allah also had to make decisions on the basis of factionalism. I submitted that the Holy Prophet (SWS) has inculcated honesty and justice in his dealings with non-Muslims and has taught morality in every matter. He has taught to strike a balance in dealing with non-Muslims. may Allah Almighty grant us the ability to follow the sunnah of the Prophet in the true sense.